A novel dual-responsive halloysite nano-container for anti-corrosion coatings. Issue 3 (16th February 2022) - Liu, Yuanwei; Wang, Bin; Xie, Yan; Chen, Yu; Yang, Zhongnian; Han, Guojun; Dang, Yanqiu
Abstract : Purpose: The purpose of this paper is to prepare a dual-encapsulated halloysite nano-container to release the capsuled inhibitor as an additive for corrosion protection of epoxy coating. Design/methodology/approach: Halloysite nano-containers (HNT) were prepared by simultaneously implanting inhibitor benzotriazole (BTA) into the inside and outside of the halloysite using reduced pressure and layer-by-layer (LBL) assembly, respectively. The microstructure and morphology of treated HNT were investigated using Fourier transform infrared spectroscopy and transmission electron microscopy. In addition, the anti-corrosion behaviors of the composite polyepoxy coating with inhibitor-loaded nano-containers BTA@HNT-2 were investigated using the electrochemical impedance spectroscopy and neutral salt spray test. Findings: Test results showed that the LBL assembly structure of the halloysite nano-container makes the BTA@HNT-2 nano-container be controlled and sustained to release BTA, relying on the pH. Very importantly, the obtained nano-container is also responsive to temperature, owing to the thermosensitivity polyelectrolyte out-shell of the HNT. The result showed R ct of the composite polyepoxy coating can be sufficient to maintain higher than 8.510E+7 Ω·cm 2 over 72 h of immersion test. Moreover, the artificial induced defects on the coating surface were sufficiently inhibited in the presence of BTA@HNT-2 nano-container in the polyepoxy coating. Originality/value: Use of the BTA@HNT-2 as corrosion inhibitor nano-container, with good anti-corrosion property and dual-responsive to pH and temperature, offers a significant rout to prepare smart anti-corrosion coating for protecting metal substrate.